Hubungan Asupan Energi dan Zat Gizi Makro dengan Status Gizi Anak Sekolah Dasar (SD) Muhammadiyah di Kabupaten Gresik: Hubungan Asupan Energi dan Zat Gizi Makro dengan Status Gizi Anak Sekolah Dasar Muhammadiyah di Kabupaten Gresik - Sholikhah, Desty Muzarofatus; Rahma, Amalia (Universitas Airlangga, 2024)
Background: School-age children are vulnerable to nutritional and health problems. Several factors that can directly influence a child's nutritional status are nutritional intake, which includes energy and macronutrient intake, level of physical activity, and incidence of illness. Objectives: This research analyzes the relationship between energy intake and macronutrients with the nutritional status of Muhammadiyah elementary school children in Gresik Regency. Methods: This research was an observational analytical study with a cross-sectional study design. Using purposive sampling, 231 children from five Muhammadiyah elementary schools in Gresik Regency were taken as research samples. The research was carried out from May to June 2023. Research variables include energy intake, intake of macronutrients, and nutritional status. Data collection used the interview method with 2x24-hour food recall, FFQ (Food Frequency Questionnaire), and measuring body weight and height to assess nutritional status based on BMI-for-age (Body Mass Index-for-age). All research data were analyzed using the Spearman test. Results: The result showed there is a relationship between energy intake (p-value=0.000) and protein (p-value=0.000) with nutritional status, but there is no relationship between the intake of fat (p-value=0.253) and carbohydrates (p-value=0.821) with nutritional status of Muhammadiyah elementary school children in Gresik Regency. Conclusions: Intake of energy and macronutrients, especially protein, is related to the nutritional status of school children in Gresik Regency. Healthy food and snacks need to be provided in school canteens to support the nutritional status of school-age children.